Write the path [ ] (Palíndromo, 2016)
This text is the result of an exerci- se proposed by Prof. Rosângela Cherem during the Seminar about research, in PPGAV-UDESC. It was proposed to arti- culate a dissertation or thesis, that there had been presented in previous lessons, to each one research. The text chosen is the master’s thesis of Claudio Miklos on Zen Buddhism and dematerialization. The text is developed by approaches and distances between the concepts presen- ted and my artistic production.
Keywords: conceptual art; research; Cláudio Miklos; dematerializaton